Non-immune functions of B7-H3: bridging tumor cells and the tumor vasculature - Wu, Shuo; Hu, Chenxi; Hui, Kaiyuan; Jiang, Xiaodong (Frontiers in Oncology, 2024)
B7-H3 (CD276), an immune checkpoint molecule, is overexpressed in various types of cancer and their tumor vasculature, demonstrating significant associations with adverse clinical outcomes. In addition to its well-known immune functions, B7-H3 exhibits dual co-stimulatory/co-inhibitory roles in normal physiology and the tumor microenvironment. The non-immune functions of B7-H3 in tumor cells and the tumor vasculature, including promoting tumor cell anti-apoptosis, proliferation, invasion, migration, drug resistance, radioresistance, as well as affecting cellular metabolism and angiogenesis, have increasingly gained attention from researchers. Particularly, the co-expression of B7-H3 in both tumor cells and tumor endothelial cells highlights the higher potential and clinical utility of therapeutic strategies targeting B7-H3. This review aims to summarize the recent advances in understanding the non-immune functions of B7-H3 in tumors and provide insights into therapeutic approaches targeting B7-H3, focusing on its co-expression in tumor cells and endothelial cells. The aim is to establish a theoretical foundation and practical reference for the development and optimization of B7-H3-targeted therapies.